Looking for New P Fertilizers: Comparative Study of Mineral-, Organomineral- and Organic-Based Fertilizers for Lettuce (Lactuca sativa L.) - Lucía Valverde-Vozmediano; Silvia Sánchez-Méndez; Luciano Orden; Miguel A. Mira-Urios; Francisco Javier Andreu; Jose A. Sáez; Encarnación Martínez-Sabater; María Ángeles Bustamante; Javier Martín-Pozuelo; Raúl Moral (Agronomy, 2025)
In this study several phosphorus fertilizers were evaluated under controlled production conditions using Lactuca sativa var. baby leaf and a clay-loam soil of pH 6.5 as a plant–soil model system. Various inorganic (phosphate rock, monoammonium phosphate, struvite), organic (bone meal and bone meal pelletized with compost) and organomineral fertilizers (phosphate rock, monoammonium phosphate, struvite pelletized with compost) were compared. The soil properties, crop yield, morphological aspects and metabolomics of the plants were analyzed. After 45 days of the growing cycle, the organomineral fertilizers (OMFs) composed of compost and monoammonium phosphate (OMF2(MAP+C)) or struvite (OMF3(STR+C)) exhibited the best yield results: 101.37 g and 83.21 g, respectively. These treatments also exhibited the best phosphorus use efficiency (PUE) results: 7.40% and 8.33%, respectively. The yield of plants treated with MAP was 56.01 g, and its PUE was 5.33%. The yield of plants treated with STR was 62.10 g and the PUE was 4.67%. Accordingly, the development of OMFs with compost had a positive effect regarding MAP and STR fertilization. Lettuce fertilized with organic bone meal fertilizers had the lowest yield and nutrient use efficiency. The non-targeted metabolic study of green tissue revealed an overactivation of the TriCarboxylic Acids-TCA cycle and amino acid biosynthesis in plants fertilized with bone meal and phosphate rock treatments, likely as a plant stress response. The overall conclusion of this work is that the development of OMFs with compost is a good strategy to increase soil P availability and, accordingly, plant P uptake and %PUE.